2020
DOI: 10.7554/elife.58142
|View full text |Cite
|
Sign up to set email alerts
|

Spectral clustering of risk score trajectories stratifies sepsis patients by clinical outcome and interventions received

Abstract: Sepsis is not a monolithic disease, but a loose collection of symptoms with diverse outcomes. Thus, stratification and subtyping of sepsis patients is of great importance. We examine the temporal evolution of patient state using our previously-published method for computing risk of transition from sepsis into septic shock. Risk trajectories diverge into four clusters following early prediction of septic shock, stratifying by outcome: the highest-risk and lowest-risk groups have a 76.5% and 10.4% prevalence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…We repeated our analyses of risk score trajectories for stratification of sepsis patients ( 16 ). Spectral clustering ( 27 ) of risk score trajectories in the window surrounding early prediction yielded two clusters ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We repeated our analyses of risk score trajectories for stratification of sepsis patients ( 16 ). Spectral clustering ( 27 ) of risk score trajectories in the window surrounding early prediction yielded two clusters ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we found that entry into preshock was marked by a rapid transition from low to high risk. Prior to entry, patient physiology was indistinguishable between the low- and high-risk clusters ( 16 ). However, after entry into preshock, risk score trajectories diverged and stratified patients by risk of septic shock, mortality, time to septic shock onset, and treatments received.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clustering methods are one way to try and solve this issue. They have been applied to the evolution of sepsis in very large studies 45 but also on the scale of a few hundred patients 5 . Leijte et al 46 carried out a detailed analysis of mHLA-DR expression kinetics in a large cohort of 241 septic shock patients over the first week after injury.…”
Section: Introductionmentioning
confidence: 99%